Characteristic Patients with Multiple Myeloma at Dr. Kariadi Hospital Semarang - Santosa Iva; Catharina Soeharti; Mika Lumban Tobing; Suyono Suyono; Eko Adhi Pangarsa (Acta Interna The Journal of Internal Medicine, 2015)
Background. Multiple myeloma (MM) is a malignancy of differentiated B-lymphocytes characterized by accumulation of clonal plasma cells in the bone marrow (BM), the presence of a monoclonal immunoglobulin (Ig) in the serum and/or urine, and osteolytic bone lesions. Complications of this disease consist of recurrent bacterial infection, anemia, osteolytic lesion and decreased renal function. 2-5 MM is the cause of death in 1% of cancer death in Western countries. MM incidence is 1% of all malignancies and 10% of hematologic malignancies in Caucasian race and 20% in the Afro American race.Aim. The aim of the study is to know the descriptive data of characteristic of patients with MM at dr. Kariadi Hospital Semarang.Method. Despite of development in patient management, MM is still an incurable disease, with 5-year survival rates lower than 40%. There are many differences in myeloma and its clinical manifestations. Some patients can survive in the months until over than 10 years.5, 6, 7 The median survival was 33 months, this number is similar in Asian studies.Results. There are several prognostic factors in myeloma management, such as β2-Microglobulin (β2m), serum albumin, serum creatinine, plasma cell percentage in marrow, bone lytic lesion, anemia.10-13 β2m is a prognostic factor used by the International Staging System (ISS)11 to determine stadium and prognosis in MM. β2m correlates with other prognostic factors, such as serum creatinine, anemia, mechanism of bone destruction in MM patients.11,13Conclusion. MM in Indonesia has not been studied comprehensively and the β2m measurement is expensive and not widely available.